The Counseling Relationship Assessment Measure (CRAM): Initial Validation and Psychometric Properties - Fuertes, Jairo; Moore, Michael; Bhatti, Usama (Journal of Assessment and Research in Applied Counseling (JARAC), 2026)
Purpose: A new assessment of the counseling relationship is presented, which is needed given the limitations of current assessments in the literature. Method: The research team developed 100 items to assess these three factors from the perspective of the counselor (50 items) and the client (50 items) then had 12 professional counselors serve as content validity judges. Based on their feedback, several items were deleted or modified. The modified assessment measures were then sent to 168 counselors and to 252 clients. Exploratory Structural Equation Modeling (ESEM) and then Confirmatory Factor Analysis (CFA) were used to examine their factors structure. Results: Analyses yielded two 6 items versions of the assessment measure (i.e., client and counselor forms), comprised of the underlying constructs of Frame Consensus, Collaborative Motivation, and Collaborative Action. Both forms displayed strong psychometric properties indicative of reliability and validity. Conclusions: The new measure can be used as a complement to or as an alternative to existing measures of the counseling relationship in research or practice.